Rankings and the Public Good Role of Higher Education - Hazelkorn, Ellen (International Higher Education, 2019)
Measuring university engagement or societal impact is becoming a popular way to assess the public good role of universities. Rankings have been early movers in this area, but do they tell us anything meaningful? And while it is important to ask about the role and responsibility of universities, it is about time that we asked about the corporate social responsibility (CSR) of the ranking organizations themselves, given that their real intent is to sell magazines and newspapers and/or consultancy?